A Comparison of the Thoughts of Hadith Hermeneutics Figures Fatimah Mernessi and Syuhudi Isma'il - Ichwayudi, Budi; Alfani, Mukhammad (ISLAMIKA, 2024)
This article discusses the comparison of Hadith Hermeneutics thought between two prominent figures, namely Fatimah Mernessi and Muhammad Syuhudi Isma'il. Both have similarities in understanding Hadith in a socio-historical manner, but have differences in the focus of study and methods of analysis. Hadith Hermeneutics is a new breakthrough in finding answers to new problems that arise in modern times. The journal Islamika, a journal of Islamic and educational science, is a place to discuss the comparative thinking of the two figures. The method used is the comparative method to find out the similarities and differences between the thoughts of Fatimah Mernessi and Muhammad Syuhudi Isma'il. This article also reviews the biography and thoughts of Fatimah Mernissi and her academic career. Fatimah Mernissi, a well-known writer whose works have been translated into various languages, has a deep interest in misogynistic hadiths. She strongly emphasizes the need for intense research into the Prophetic Hadiths, and her work deals with sex and the role of women, women and politics, women's leadership, and women/angels and paradise. Mernissi opposes the patriarchal system that gives men dominance in various aspects of life, with women often being neglected. On the other hand, Muhammad Syuhudi Isma'il, an intellectual in Indonesia, has contributed greatly to the development of hadith science. He taught the evolutive and dynamic concept of sunnah and divided hadith based on their context. He also identified asbab al-wurud in understanding hadith. From this comparison, it can be concluded that both figures made important contributions in eliminating stereotypes against women.